1981
DOI: 10.1007/bf01531683
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of auditory stimulus processing in normal and autistic adolescents

Abstract: This experiment investigated the possibility that autistic adolescents may avoid speech communication with the world around them by "tuning out" or perceptually suppressing auditory speech stimuli. The tune-out auditory suppression hypothesis was investigated using the subject's own speech as the stimulus under three perceptual-motor conditions: with speech in a delayed auditory feedback (DAF) mode, with a white noise masking speech mode, and with speech in a normal, quiet listening mode. Five autistic adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In addition, a previous study using pitch-shifted auditory feedback also found that a subgroup of individuals with ASD have larger responses to perturbed auditory feedback ( Russo et al, 2008 ), which indicates that some individuals with ASD rely more on feedback control than on feedforward control in speech production. Another previous study found no difference between the ASD group and the control group for DAF and the Lombard effect ( Nober and Simmons, 1981 ), but they only tested a small number of participants. Here we tested a larger number of participants.…”
Section: Introductionmentioning
confidence: 88%
“…In addition, a previous study using pitch-shifted auditory feedback also found that a subgroup of individuals with ASD have larger responses to perturbed auditory feedback ( Russo et al, 2008 ), which indicates that some individuals with ASD rely more on feedback control than on feedforward control in speech production. Another previous study found no difference between the ASD group and the control group for DAF and the Lombard effect ( Nober and Simmons, 1981 ), but they only tested a small number of participants. Here we tested a larger number of participants.…”
Section: Introductionmentioning
confidence: 88%
“…Lombard's results have been used as a diagnostic test for unilateral deafness, false or exaggerated hearing loss (‘pseudohypacusis’), and other hearing pathologies (Lane & Tranel, ; Nober & Simmons, ; Brumm & Zollinger, ), and to develop speech recognition technologies (Junqua, , ; Junqua, Fincke & Field, ). Such practical applications have generated high levels of interest from medical professionals and software engineers, leading to detailed understanding of specific characteristics of the Lombard effect in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In the years since Lombard's initial discovery, the relationship between increased noise level and vocalization amplitude has come to be known mainly as the 'Lombard effect' (but is also referred to as: the Lombard sign, function, reflex, phenomenon, response, or reaction) (Egan, 1967;Brumm & Zollinger, 2011). Lombard's results have been used as a diagnostic test for unilateral deafness, false or exaggerated hearing loss ('pseudohypacusis'), and other hearing pathologies (Lane & Tranel, 1971;Nober & Simmons, 1981;Brumm & Zollinger, 2011), and to develop speech recognition technologies (Junqua, 1993(Junqua, , 1996Junqua, Fincke & Field, 1999). Such practical applications have generated high levels of interest from medical professionals and software engineers, leading to detailed understanding of specific characteristics of the Lombard effect in humans.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, with respect to the acoustic processing of language, children and young adults with ASD performed as well as their peers in a phonological production task (Bishop et al 2004), including in situations with stressful auditory input (Nober and Simmons 1981), and they also perceived native and non-native phoneme contrasts as well as their peers (Constantino et al 2007). In the related domain of prosody, the results are mixed.…”
Section: Dialect Perception By Typically Developing Adultsmentioning
confidence: 98%